Faktor Risiko Hipotermia Pasca Anestesi Umum di Instalasi Bedah RSUD Regina Maris Medan - Welong S. Surya; Nilawati Nilawati (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Hypothermia after general anesthesia is a common complication that can seriously impact patient recovery. Identifying risk factors contributing to this occurrence is crucial for effective prevention and management. Objective: To determine the risk factors associated with the occurrence of hypothermia after general anesthesia in patients in the Surgical Unit of Regina Maris Regional Hospital, Medan. Methods: This study used a quantitative analytical design with a cross-sectional approach. A sample of 78 patients undergoing general anesthesia was selected using a purposive sampling technique. Data were collected through observation and documentation, and analyzed using the Chi-square test. Results: Factors shown to be significantly associated with the occurrence of hypothermia after general anesthesia included preoperative body temperature (p=0.010), gender (p=0.014), and duration of surgery (p=0.001). Meanwhile, age and body mass index did not show a significant association. Conclusion: Body temperature, gender, and duration of surgery are the main determinants of the occurrence of hypothermia after general anesthesia. Preventive strategies that focus on body temperature management before and during surgery are needed, especially in high-risk patients.